KONSEP KEPEMIMPINAN DALAM ISLAM - Fridiyanto, Fridiyanto (Jurnal Ilmiah Al-Hadi, 2020)
Leadership is key in managing an organization, therefore in the management field, it must be studied. Many leadership research is produced by management researcher but it is still lack in studying Islam concepts. This article argues that Islamic leadership to guide ummah, justice, humanity and love each other. Muhammad Prophet is an ideal leader model, therefore the managers and leaders should follow his leadership.